Measurement of the CP-violating phase ϕ(s) in the decay B(s)(0) → J/ψϕ. - Aaij, R; Abellan Beteta, C; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Alkhazov, G; Alvarez Cartelle, P; et al. (2012)
We present a measurement of the time-dependent CP-violating asymmetry in B(s)(0) → J/ψϕ decays, using data collected with the LHCb detector at the LHC. The decay time distribution of B(s)(0) → J/ψϕ is characterized by the decay widths Γ(H) and Γ(L) of the heavy and light mass eigenstates, respectively, of the B(s)(0) - B(s)(0) system and by a CP-violating phase ϕ(s). In a sample of about 8500 B(s)(0) → J/ψϕ events isolated from 0.37  fb(-1) of pp collisions at sqrt[s] = 7  TeV, we measure ϕ(s) = 0.15 ± 0.18(stat) ± 0.06(syst)  rad. We also find an average B(s)(0) decay width Γ(s) ≡ (Γ(L) + Γ(H))/2 = 0.657 ± 0.009(stat) ± 0.008(syst)  ps(-1) and a decay width difference ΔΓ(s) ≡ Γ(L) - Γ(H) = 0.123 ± 0.029(stat) ± 0.011(syst)  ps(-1). Our measurement is insensitive to the transformation (ϕ(s),ΔΓ(s)) ↦ (π - ϕ(s), -ΔΓ(s)).